Macroeconomic Determinants of Tax Revenue and Tax Effort in Southeast Asian Countries - Saptono, Prianto Budi; Mahmud, Gustofan (Universitas Airlangga, 2021)
This paper analyzes macroeconomic indicators that determine tax revenues in six Southeast Asian countries during 2008 – 2019. The estimation results are then used to predict the value of taxable capacity to construct the deal of tax effort. Using the FE model equipped with the Driscoll-Kraay standard errors, this study finds positive and significant effects of per capita income, manufacturing, and trade openness on the actual tax-to-GDP ratio and tax effort. In contrast, inflation is considered a different determinant because of its insignificant effect on the two measures of tax performance. In addition, the authors also classify countries into three other groups based on the actual level of tax revenue and the effort put into collecting taxes. The benchmarks used to rank countries are all sample countries' median substantial tax revenue and the tax effort index 1. Regardless of the classification, several policy implications are offered to increase tax collection productivity by focusing on the revenue bases used in the estimation model. Keywords: Tax Revenue, Tax Capacity, Tax Effort, Southeast Asia, Panel DataJEL: H2, O1, O2